Functional integrity of freshwater forested wetlands, hydrologic alteration, and climate change. Issue 1 (2nd February 2016) - Middleton, Beth A.; Souter, Nicholas J.
Abstract: Climate change will challenge managers to balance the freshwater needs of humans and wetlands. The Intergovernmental Panel on Climate Change predicts that most regions of the world will be exposed to higher temperatures, CO2, and more erratic precipitation, with some regions likely to have alternating episodes of intense flooding and mega‐drought. Coastal areas will be exposed to more frequent saltwater inundation as sea levels rise. Local land managers desperately need intra‐regional climate information for site‐specific planning, management, and restoration activities. Managers will be challenged to deliver freshwater to floodplains during climate change‐induced drought, particularly within hydrologically altered and developed landscapes. Assessment of forest health, both by field and remote sensing techniques, will be essential to signal the need for hydrologic remediation. Studies of the utility of the release of freshwater to remediate stressed forested floodplains along the Murray and Mississippi Rivers suggest that brief episodes of freshwater remediation for trees can have positive health benefits for these forests. The challenges of climate change in forests of the developing world will be considered using the Tonle Sap of Cambodia as an example. With little ecological knowledge of the impacts, managing climate change will add to environmental problems already faced in the developing world with new river engineering projects. These emerging approaches to remediate stressed trees will be of utmost importance for managing worldwide floodplain forests with predicted climate changes.